Effects of Splenectomy on Spontaneously Chronic Pancreatitis in aly/aly Mice. (9th March 2010) - Wang, Heng-Xiao; Yi, Shuang-Qin; Li, Jun; Terayama, Hayato; Naito, Munekazu; Hirai, Shuichi; Qu, Ning; Yi, Nozomi; Itoh, Masahiro
Abstract : Background and Aim . Mice with alymphoplasia ( aly/aly ) mutation characterized by a lack of lymph nodes, Peyer's patches, and well-defined lymphoid follicles in the spleen were found. In this study, we used splenectomized aly/aly mice to elucidate the effects of secondary lymphoid organs in the development of aly/aly autoimmune pancreatitis. Methods . Forty-eight 10-week-old aly/aly mice were divided into two groups for splenectomy and sham operation. Histological and immunohistochemical analyses of the pancreas were performed at the ages of 20, 30, and 40 weeks old after operation, respectively. Results . Our results showed that mononuclear cell infiltration was restricted to the interlobular connective tissues at the age of 20 weeks, and not increase obviously at the age of 30 and 40 weeks in splenectomized aly/aly mice. Furthermore, an apparent decrease in the expressions ofCD 4 + T, CD 8 + T, and B cells was detected in the pancreatic tissues compared with sham aly/aly mice, however, no significant difference in macrophage expression between mice with and without a splenectomy. Conclusions . Inflammation infiltration and development of the pancreatitis in aly/aly mice were suppressed effectively after splenectomy, which was, at least partly, correlated to inhibition of the infiltration of T and B cells in pancreatic tissues but not to macrophages.